2007
DOI: 10.1080/02770900701344199
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Efficacy of Zileuton Controlled-Release Tablets as Adjunctive Therapy to Usual Care in the Treatment of Moderate Persistent Asthma: A 6-Month Randomized Controlled Study

Abstract: This study was conducted to assess the safety and efficacy of zileuton controlled release [CR] 1,200 mg BID added to usual care (UC) in 926 patients with moderate asthma (619 patients randomized to zileuton CR and 307 to placebo). Sustained improvements in AM and PM peak expiratory flow (PEF) were observed in the zileuton CR group compared to placebo. The adverse event profile was similar in the two treatment groups. Eleven patients (1.8%) receiving zileuton CR and 2 (0.7%) receiving placebo experienced elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Unfortunately, zileuton – the only marketed inhibitor of LT biosynthesis – has not been widely used because of 1) the initial need to take it 4 times daily (a controlled-release tablet can now be used twice daily) and 2) the requirement for liver function test monitoring due to possible hepatocellular injury [112]. In addition, although no head-to-head comparisons between zileuton and a LTRA have ever been conducted, there is no compelling evidence that zileuton is typically superior to LTRAs in asthma treatment [113, 114]. Incomplete efficacy may be due to the incomplete inhibition (26 to 86 % inhibition) of LT synthesis by zileuton [115].…”
Section: Anti-lt Drugsmentioning
confidence: 99%
“…Unfortunately, zileuton – the only marketed inhibitor of LT biosynthesis – has not been widely used because of 1) the initial need to take it 4 times daily (a controlled-release tablet can now be used twice daily) and 2) the requirement for liver function test monitoring due to possible hepatocellular injury [112]. In addition, although no head-to-head comparisons between zileuton and a LTRA have ever been conducted, there is no compelling evidence that zileuton is typically superior to LTRAs in asthma treatment [113, 114]. Incomplete efficacy may be due to the incomplete inhibition (26 to 86 % inhibition) of LT synthesis by zileuton [115].…”
Section: Anti-lt Drugsmentioning
confidence: 99%
“…Hepatitis has been reported with chronic zafirlukast which resulted in hepatic failure requiring liver transplant and death. The chronic use of zileuton use has also resulted in elevated liver enzymes in about 5 % of asthma patients [79,80].…”
Section: Leukotriene Modulatorsmentioning
confidence: 99%
“…This is the same level of sequence identity observed between 5-LOX and its closest intra-species orthologue 15-LOX-2. Human 5-LOX is the only clinically validated drug target of the LOX family, but the enzyme’s short half-life has made biochemical characterization difficult (Carter et al, 1991; Percival, Denis, Riendeau, & Gresser, 1992; Wenzel et al, 2007). The extraordinary stability of the coral enzyme makes it a highly tractable system for structural studies, as protein instability is a frequent roadblock to structural studies (Deller, Kong, & Rupp, 2016), and 8 R -LOX structures have revealed key mechanistic details of the LOX oxygenation reaction.…”
Section: Introductionmentioning
confidence: 99%